The Presence of Soybean Plant Insects (Glycines Max L. Merril) in the Vegetative Phase with the Application Treatment of Streptomyces sp. and Trichoderma sp. - Nugraha Iqbal Avrianto; Penta Suryaminarsih; Wiludjeng Widajati (Nusantara Science and Technology Proceedings, 2021)
Soybean (Glycine max (L.) Merill) is one of the main food crops in the community. In East Java, productivity has declined due to various factors, including pest attacks. This study aims to determine the diversity of insects by administering a mixture of biological control agents (BSAs) between Streptomyces sp. and Trichoderma sp. as an entomopathogen applied to soybean plants in the vegetative phase. The soybean plants were planted in plastic bags on the ground of the Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran Jawa Timur. The aim of this study was to determine the effect of Streptomyces sp. and Trichoderma sp. the type and population of parasites. This study used a randomized two-way block design of 13 treatments repeated 3 times. Based on the observations, the total number of insects found in the experimental field of UPN veterans Jawa Timur was 2,360 individuals, made up of six orders of insects. The four orders are divided into 8 families and 8 species. Hemiptera species became the most dominant order (2202 individuals; 93%), Orthoptera (108 individuals; 5%), Lepidoptera (18 individuals; 1%) and Diptera (32 individuals; 1%) . The use of Streptomyces sp. and Trichoderma sp. the single comparison treatment is more effective than the combined comparison on the pest population. The main insects include Aphid spp, Bemisia tabaci and Nezera viridula.